Antioxidant effects of hydroalcoholic and polyphenolic extracts of Peucedanum pastinacifolium Boiss. & Hausskn. - Ahmad Movahedian; Behzad Zolfaghari; Mehrzad Mirshekari (Wolters Kluwer Medknow Publications, 2016)
Antioxidant activity of Peucedanum pastinacifolium Boiss. & Hausskn aerial part hydroalcoholic extract (HAE) and polyphenolic extract (PPE) as well as their total phenolic and flavonoid contents were studied. Phenolic and flavonoid contents were respectively estimated as gallic acid and quercetin equivalents. The in vitro antioxidant activity of two extracts of P. pastinacifolium were evaluated by radical scavenging of 1,1-diphenyl-2-picryl hydrazyl radical (DPPH), chelating activity on ferrous ions, or ferric reducing antioxidant power (FRAP) assay. In addition, the in vivo antioxidant activity of hydroalcoholic extract was measured by FRAP assay. Total phenolic contents of PPE and HAE were 117.1 ± 6.2 and 44.3 ± 1.7 mg/g, respectively. Total flavonoid content of PPE (43.4 ± 2.1 mg/g) was found to be higher than that of HAE (8.0 ± 1.5 mg/g). In DPPH radical scavenging assay, HAE and PPE showed fifty percent inhibitory concentration (IC 50 ) values of 469.4 ± 9.3 µg/mL and 128.2 ± 5.5 µg/mL, respectively. Iron chelating activity assays indicated IC 50 values of 657.5 ± 13.2 µg/mL and 735.4 ± 16.1 µg/mL for HAE and PPE as opposed to ethylenediamine tetra-acetic acid (EDTA) being 16.5 ± 0.8 µg/mL. PPE exhibited greater FRAP value (154.0 ± 1.8 µM) as compared with that of HAE being 69.3 ± 1.4 µM. In animal study, HAE showed a significant (p < 0.05) increase in FRAP level when compared with that of control group. Our results showed that P. pastinacifolium possess antioxidant properties which most likely are exerted through free radical scavenging, chelating activity, and reducing power.